2000
DOI: 10.1590/s0100-879x2000000600011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the kinin receptors after induction of myocardial infarction: a mini-review

Abstract: It is well known that the responses to vasoactive kinin peptides are mediated through the activation of two receptors termed bradykinin receptor B1 (B1R) and B2 (B2R). The physiologically prominent B2R subtype has certainly been the subject of more intensive efforts in structure-function studies and physiological investigations. However, the B1R activated by a class of kinin metabolites has emerged as an important subject of investigation within the study of the kallikreinkinin system (KKS). Its inducible char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
1
36
0
1
Order By: Relevance
“…Up-regulation of the B1 receptor expression has been observed to reach its maximum at 24 hours and quickly reduced to a barely detectable level at 6 days after MI. However, expression of the B2 receptor in the left ventricle after MI reaches a peak at 24 hours and remains high for at least 6 days, suggesting the main role of the B2 receptor at the sub-acute remodeling phase after MI [32]. Neutrophil migration in inflamed tissues is reduced in kinin B1 knockout mice, indicating that the pro-inflammatory effect of kinin is mediated by the B1 receptor [33].…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of the B1 receptor expression has been observed to reach its maximum at 24 hours and quickly reduced to a barely detectable level at 6 days after MI. However, expression of the B2 receptor in the left ventricle after MI reaches a peak at 24 hours and remains high for at least 6 days, suggesting the main role of the B2 receptor at the sub-acute remodeling phase after MI [32]. Neutrophil migration in inflamed tissues is reduced in kinin B1 knockout mice, indicating that the pro-inflammatory effect of kinin is mediated by the B1 receptor [33].…”
Section: Discussionmentioning
confidence: 99%
“…41,42,55 In such cases, the B 1 R can take over some of the vasodilatory functions of the B 1 R, but not its metabolic (insulin-sensitizing) function. It was recently reported that in hearts from subjects with end stage cardiac failure, the expression of B 1 Rs was significantly increased both at the mRNA and the protein level 56,57 in contrast to the B 2 Rs, which were found to be significantly downregulated. 58 A plausible explanation for these findings is that increases in expression and activity of the B 1 R may be partly triggered by inflammatory cytokines, such as TNF-a, whose levels increase in chronic heart failure [59][60][61] and chronic tissue injury, but may also represent a compensatory reaction to diminished functional capacity of the B 2 R. At this time it is unclear whether the upregulation of the B 1 R under these circumstances may be beneficial by enhancing regional blood flow, thus contributing to tissue protection, or may actually have a detrimental effect by interacting with inflammatory mediators and further exacerbating the inflammatory process.…”
Section: Bradykinin Receptorsmentioning
confidence: 95%
“…53 Furthermore, ACE itself can also upregulate the gene expression of both BK receptors by up to 11-22 fold, via a mechanism apparently unrelated to its enzymatic properties. 66 It was reported that in myocardial tissues of rats submitted to acute myocardial infarct there was a significant upregulation of both B 1 R and B 2 R detectable within 6 h and reaching its peak at 24 h, 57,67,68 with the B 1 R expression returning gradually to baseline in the next 3-6 days, whereas the B 2 R overexpression appears to last much longer. Thus, myocardial ischemia-whether due to Ang II-induced coronary constriction or to mechanical coronary obstruction-is associated with an upregulation of both BK receptors that would seem to be compensatory, but may also have noxious effects as well.…”
Section: B 2 R-mediated Cardioprotection Post Ischemic Injurymentioning
confidence: 99%
“…Several authors have reported increased endogenous levels of kallikrein (KLK), kininogen, and bradykinin (BK) and an upregulation of B 1 and B 2 receptors in response to cardiac ischemia (1,12,15,18,25,34,35). Direct application of BK in perfusion medium improves cardiac left ventricular (LV) function, coronary flow, and myocardial metabolism and reduces the infarct size of isolated working rat hearts during and after induction of myocardial ischemia via activation of the prostaglandin and nitric oxide (NO) axis (36). Likewise, the inhibition of kinin breakdown by kininase inhibitors has been shown to exert cardioprotective effects in in vivo models of MI (11,42).…”
mentioning
confidence: 99%